The surface right - Del Risco Sotil, Luis Felipe (2017)
This article addresses over the regulation of the surface right in the Peruvian Law along with its main points of contact with other important institutions in the field of real estate. The author points the evolution of this figure in the Peruvian legislation and determinates its legal nature and its characteristics, establishing its relation with the principle of real estate accession property and the implications of the transitional division that the surface generates. In other relevant aspects, the article addresses the ways of acquisition of such ownership, the role of inscription in the configuration of the surface, the reimbursement of the value of the buildings and the extinction of this property right.